Homeownership and Entrepreneurship: The Role of Mortgage Debt and Commitment - Philippe Bracke; Christian Hilber; Olmo Silva (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study the link between homeownership, mortgage debt, and entrepreneurship using a model of occupational choice and housing tenure where homeowners commit to mortgage payments. Our model predicts that, as long as mortgage rates exceed the rate of interest on liquid wealth: (i) mortgage debt, by amplifying risk aversion, diminishes the likelihood that homeowners start a business; and (ii) the negative relation between mortgage debt and entrepreneurship is more pronounced when income volatility is higher. Our model further predicts that the relation between housing wealth and entrepreneurship is ambiguously signed because of competing portfolio and hedging considerations. Exploiting the longitudinal dimension of the British Household Panel Survey to control for unobservables, we test and confirm these predictions. A one standard deviation increase in leverage makes a homeowner 10-12 percent less likely to become an entrepreneur.
Keywords: L26; D14; G11; R21; 330; entrepreneurship; homeownership; mortgage debt; leverage; commitment